2020
DOI: 10.1038/s41598-020-63040-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating RNA Transcriptome of Pregnant Women with TSH Just Above the Trimester-Specific Reference and its Correlation with the Hypertensive Phenotype

Abstract: During gestation, a woman's body undergoes physiological changes that alter thyroid function. pregnant women with hypothyroidism may exhibit gestational complications, including hypertension and preeclampsia. We investigated differentially expressed genes (DEGs) in circulating RNAs from pregnant women with tSH levels just above the normal range to determine the impact of a mild elevation of TSH in pregnancy. We selected three women with healthy thyroid pregnancy (HTP), three pregnant women with gestational hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…It is uncertain whether GHT is associated with increased cfDNA concentrations. Notably, Hirata et al studied differentially expressed genes in the circulating RNA of pregnant women with TSH levels marginally higher than the normal range and found that high levels of circulating RNA could be detected, even in women with mildly elevated TSH ( 12 ). SLE is an autoimmune disease that causes damage in parts of the body, including skin, kidneys, and joints and is characterised by the production of antibodies against nuclear antigens known as “anti-nuclear antibodies.” Recent research has shown that compared with healthy controls, SLE patients have higher cfDNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain whether GHT is associated with increased cfDNA concentrations. Notably, Hirata et al studied differentially expressed genes in the circulating RNA of pregnant women with TSH levels marginally higher than the normal range and found that high levels of circulating RNA could be detected, even in women with mildly elevated TSH ( 12 ). SLE is an autoimmune disease that causes damage in parts of the body, including skin, kidneys, and joints and is characterised by the production of antibodies against nuclear antigens known as “anti-nuclear antibodies.” Recent research has shown that compared with healthy controls, SLE patients have higher cfDNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found 1656 DEGs in healthy-thyroid pregnancy (HTP) using a healthy nonpregnant woman set, showing the physiologic mechanism regulated by genes in a healthy pregnancy [29]. Three hundred and four ORs found in HTP were similar between GHT and PEC, and all were upregulated in a healthy pregnancy condition (Supplementary Table S1).…”
Section: Olfactory Receptor Familymentioning
confidence: 99%